Framing and Intermedium Practices in Islamic Apologetics: The Construction of Religious Identity and Multicultural Dynamics on Bang Zuma’s YouTube Channel - Iman Mukhroman; Deni Miharja (Parahyangan Catholic University, 2025)
This article aims to analyze the construction of religious identity through intermedial practices and framing strategies in Islamic apologetic content on social media. The study focuses on the Official Bang Zuma YouTube channel, which presents Islamic apologetics through a combination of audio, visual, textual, and online interaction. The research employs a qualitative content analysis method, integrating Robert Entman’s framing theory and Thierry de Duve’s intermedium approach to examine how messages are structured, transmitted, and received by audiences. The findings indicate that Bang Zuma’s apologetic content frames Islam as occupying a defensive position perceived as threatened yet theologically superior, while employing intermedial techniques to reinforce narratives and construct a virtual interpretive community. Three key results emerge: (1) framing-intermedium practices strengthen group identity boundaries and produce a model of “segregative multiculturalism”; (2) although predominantly confrontational, apologetic content leaves room for constructive dialogue through the presence of “digital mediators” among followers; and (3) the development of “multicultural digital literacy” is required to balance the polarizing potential of apologetic content. The implications highlight the importance of inclusive digital literacy strategies to strengthen social cohesion in the era of new media. The originality of this study lies in its integration of framing theory and the intermedium approach to explain how religious identity is shaped within the contemporary digital landscape and its implications for the dynamics of multiculturalism in Indonesia.